Not All Fun and Games. (Communications of the ACM, 2005)
This article focuses on news related to the video game industry. The video game industry is exploding, with a global market that was expected to exceed $35 billion by year-end 2004. The bad news is the legion of programmers working under pressure to churn out hits for the game industry is burning out at a rapid rate. A recent survey by the International Game Development Association found nearly 60% of the respondents claiming crunch periods of overtime were commonplace, yet 47% said they were not compensated for putting in the extra time. Indeed, only 3% of those surveyed said their employers even counted the overtime hours they worked. "There's a cowboy mentality about working 60 to 80 hours a week, drinking Jolt Cola to stay awake, and being a game development machine," said a spokesperson for the association. Some companies exploit that and pressure people to work long hours.